Regulatory Justice Review Compensation in Criminal Case According to the Criminal Procedure Code - Parlagutan, Dodi; Supardi, (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
This research examines the regulation of compensation in criminal cases with the rise in cases of wrongful arrest/misguided trials in Indonesia. This research aims to analyze positive law which regulates compensation for damages in criminal cases as well as analyzing existing regulations with the desired legal justice. The research method used in this research is normative juridical. The results of this research explain the emergence of injustice in the regulation of compensation in criminal cases regulated in the Criminal Procedure Code as well as Government Regulations as implementing regulations for victims of wrongful arrest/miscarriage of justice in the current laws and regulations. There is injustice for victims of wrongful arrest/misguided trials in the current regulations. For example, there is a maximum time limit for victims of wrongful arrest/deviant justice to submit a claim for compensation, the nominal amount of compensation is far from justice and does not correspond to the losses experienced by the victim and regulations that are unclear and vague have the potential to be unfair in practice. So it is necessary to update legal regulations regarding compensation that upholds the value of justice in accordance with the principles of establishing statutory regulations, namely efficiency and effectiveness. So it is hoped that the legal reform will uphold the values ​​of justice expected for victims of arrest/misguided justice. Keywords: Compensation for losses, Criminal Procedure Law, Law and Justice